Value engineering and its impact on construction projects using building information modeling - Hadi Faghihmaleki; Saman Rahimireskati; Mohamamd Darbandi (Big Data and Computing Visions)
Due to the fact that science is advancing and construction in our society is increasing, the engineering community is also obliged to introduce new approaches to the country and use them in this field. The traditional method (CAD) used to be used in this field and now the engineering community in most of the world uses Building Information Modeling (BIM) technology. BIM helps the project team observe what will be built in a simulated environment. This study examines the role of BIM in reducing time, cost savings, quality improvement, monitoring, control, estimating time and cost, comparing current conditions with standards, and reporting. We also compared the two projects, one using BIM and the other using the traditional method. The results showed that the use of BIM helps to include value engineering in projects, collisions do not occur during project implementation .